CONTRIBUTION TO THE LATE NEOGENE STRATIGRAPHY OF THE ANCIENT GORTYS AREA (SOUTHERN CENTRAL CRETE, GREECE) - Bellas, S.; Keupp, H. (Bulletin of the Geological Society of Greece, 2010)
Most of the basal Neogene sediments of Crete Island (South Aegean Sea) were unconformably deposited during synsedimentary extensional tectonics and subsequent transgression on the basement. This work mainly focuses on the marine stratigraphy of south central Crete and specifically on the sedimentary deposits of the Gortys subbasin-area located in the basin of Messara. Four selected profiles north of Gortys ancient ruins (Heraklion Province) are lithostratigraphically presented. Profiles Gortys-1 and -2 (combined to one: 1+2) represent the basal Neogene deposits (older strata-commence of sedimentation) and are interpreted as of fluviatile to lagoonal origin, while profiles Gortys-4 and - 4a are considered the younger, marine development of the Gortys subbasin. Between profiles –4 and –4a are developed evaporites of the Messinian Salinity Crisis (MSC). Profiles are biostratigraphically studied and correlated on the basis of either identified macrofossils or calcareous and siliceous nannofossils. The recorded assemblages range in age from Serravallian-Tortonian to Messinian and Zanclean respectively. The good preservation and abundance of the fossil phytoplankton establishes a well-constrained biostratigraphic framework, which will further contribute to the understanding of the evolution of the Messara sedimentary basin.